PENGARUH WAKTU HIDROTERMAL PADA SINTESIS ZEOLIT DARI ABU SEKAM PADI SERTA APLIKASINYA SEBAGAI BUILDER DETERJEN - Sholichah, Fitriani (Chem Info Journal, 2013)
Has done research on use of concerning the effect of time on the hydrothermal synthesis of zeolite from rice husk ash and its application as a detergent builder. The purpose of this study was to determine the effect of time on the character of hydrothermal zeolite synthesis are the type of zeolite crystal size and cation exchange capacity, and determine the detergency of the surfactant sodium lauryl sulfate using zeolite synthesis as a builder and compared with sodium tripolyphosphate (STPP). The method used in this research is the synthesis of zeolites include the manufacture of rice husk, manufacturing of sodium silicate, and manufacturing of sodium aluminate zeolites with various hydrothermal time 3 hours, 4 hours, 5 hours, 6 hours, and 7 hours, results obtained later in the characterization by x-ray diffraction method to determine the size and type of zeolite crystals, to determine the identification of functional groups on the zeolite with FT-IR, to determine the ratio of Si / Al using atomic absorption spectroscopy and determine the cation exchange capacity. The results of the characterization of zeolite synthesis optimum time variation of hydrothermal 7 hours with the type of zeolite Na-A and sodalite, crystal size 0.404 Î¼m, and the CEC value of 53.23 meq/100 grams. Synthesized zeolite was then used as a detergent builder and membandingakan with sodium tripolyphosphate (STPP). The process involves determining c.m.c surfactant detergency, manufacture and test a standard dirt detergency. Optimum detergency power the time variation of hydrothermal 7 hours of power by 93.76% and 70.47 detergency use of STPP